KERJASAMA GENERAL BORDER COMMITTEE MALINDO DALAM HUMAN TRAFFICKING DI PERBATASAN TAHUN 2015-2019 - Deva Ayu Trismaya (2020)
This study aims to analyze the cooperation between Malaysia-Indonesia through General Border Committee in the issue of human trafficking at the borderline in 2015-2019. The phenomenon of human trafficking that occurs in West Kalimantan-Sarawak is illegal migrant labor. There are three factors that support the occurrence of human trafficking in Indonesia, poverty, weak education, and social welfare inequality. Meanwhile, the driving factor for human trafficking in Malaysia is Malaysia's need for migrant workers in the informal sector. Another supporting factor for the occurrence of human trafficking in the Indonesia-Malaysia border region is the border region itself, which is not well guarded so as to create an illegal path for sending human trafficking. The method of this study uses a descriptive qualitative method supported by trans organized crime, human trafficking, and cooperative security. The result of this research is the formation of the GBC Malindo to address security threats in the border region in a peaceful, effective and sustainable manner. GBC's efforts in human trafficking issues in border areas are collaborating in various sectors and also in the field of operations and non-operations.